NILAI ISLAM DAN PEMBUATAN ALIANSI DALAM KEAMANAN GLOBAL: KASUS KOALISI KONTRATERORISME MILITER ISLAM (IMCTC) - Gultom, Yosua Saut Marulitua; Andara, Namira Naza; Firzatullah, Mohammad Fadhil (Department of International Relations Universitas Satya Negara Indonesia, 2024)
This research examines the role of Islamic values in the formation of global security alliances, with a focus on the Islamic Military Counter Terrorism Coalition (IMCTC). Based on the background presented, this research explains that global terrorism has become a serious threat in the post-Cold War political landscape. Counter-terrorism efforts have evolved from the Global War on Terror (GWOT) to a more inclusive approach, including the formation of alliances such as IMCTC. The research method used is qualitative and literature review, enabling an in-depth understanding of the relationship between Islamic values and security alliance formation. The findings show that IMCTC, as a military alliance led by Saudi Arabia, aims to combat terrorism by promoting peaceful and inclusive Islamic values. IMCTC seeks to create a more secure and stable environment by blending military and non-military approaches while challenging extremist narratives and encouraging moderation. This paper provides insight into the potential of Islamic values as a moral framework in combating terrorism and maintaining global stability through sustainable international cooperation.